The Private Preschool Teachers’ Perception of ICT Integration Usefulness in Teaching and Learning During MCO - Lim , Woei Jein; Aliza Ali; Mahani Abdul Malik; Nurhusna Abdul Malek (2021)
In the 21st century, one of the modern pedagogical approaches is integrating information and Communication Technology (ICT) in the early childhood curriculum. The purpose of this study is to investigate the private preschool teachers’ perception of integrating ICT and internet usage in teaching and learning during MCO in private preschools. This study employed a quantitative approach, and data collection was gathered through a survey method. A total of 44 private preschool teachers from private preschools located in the Klang Valley were selected through snowball sampling. The survey was done through questionnaires using a 5-point Likert Scale. Quantitative data were analysed through a descriptive method using the Statistical Package for The Social Science (SPSS) software. The study results indicated that young teachers have high perception of ICT integration usefulness, whereas senior teachers need to be given courses that will help them be more confident to handle children learning activities using ICT tools during MCO.